Penerapan Manajemen Waktu Untuk Meningkatkan Prestasi Belajar di SMK Panti Asuhan Yatim Piatu Al Ikhwaniyah, Jurang Mangu Barat, Tangerang Selatan - Dhea Septiani Putri; Raikha Dalimayanti; Sekar Arum Widhya N; Irfan Rizka Akbar (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Abstract. The Student Creativity Program (PKM) aims to educate and train vocational school students at the Al Ikhwaniya Orphanage, West Mangu Gap, regarding the Application of Time Management to improve learning achievement. The main problem faced by students is the difficulty of managing study time in the midst of a busy orphanage routine, which has an impact on a lack of focus and academic preparation. The activity was carried out through stages: needs analysis, material preparation, implementation of interactive training, simulation of effective learning schedule, and evaluation. The methods used are participatory training, group discussions, and direct practice of making a time schedule. The results showed an increase in students' awareness of the importance of time, a positive change in the way they prioritized, and enthusiasm to apply time management techniques (such as creating to-do lists and study schedules) to achieve better achievement. This program is expected to be a sustainable model to support orphanage students in facing the world of education and work. Keywords: Time management, Learning achievement, Training, Vocational Children, Orphanage.